2013
DOI: 10.1093/ntr/ntt043
|View full text |Cite
|
Sign up to set email alerts
|

Weight Concerns Among Finnish Ever-Smokers: A Population-Based Study

Abstract: Concern over weight gain after smoking cessation has been hypothesized to discourage quit attempts and consequently reduce smoking cessation rates. The aim of this study was to examine the association between smoking status and weight concerns among a population-based sample of Finnish ever-smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In a study of almost 2000 smokers in the USA, recruited into a trial of bupropion and/or nicotine inhalers to promote cessation, 50% of female and 26% of male smokers reported that gaining weight discouraged them from trying to quit, 2 while among adults in Finland, daily smokers were found to report more weight concerns than former smokers or occasional smokers. 3 …”
Section: Introductionmentioning
confidence: 99%
“…In a study of almost 2000 smokers in the USA, recruited into a trial of bupropion and/or nicotine inhalers to promote cessation, 50% of female and 26% of male smokers reported that gaining weight discouraged them from trying to quit, 2 while among adults in Finland, daily smokers were found to report more weight concerns than former smokers or occasional smokers. 3 …”
Section: Introductionmentioning
confidence: 99%
“…This process likely explains why smokers tend to decrease body weight, and why smoking cessation is frequently followed by weight gain. As a result, one of the barriers to quitting is the fear of gaining weight [31]. …”
Section: Discussionmentioning
confidence: 99%
“…The majority of women who quit smoking gain 8 to 10 lb on average [9][10][11][12][13]. Many women smokers report concerns about weight gain as a barrier to quitting [14][15][16][17][18][19][20][21][22][23][24][25], and women quitters who return to smoking identify weight gain as a reason for their relapse [26][27][28][29]. Women who are highly concerned about their weight are more likely to smoke as a means to control their weight [15,30,31].…”
Section: Introductionmentioning
confidence: 99%